Compact Analyzer for a Laser Time-of-Flight Mass Spectrometer. Issue 6 (December 2015) - Karpov, Alexander V.; Spakhov, Alexander V.; Sysoev, Alexander A.
Aspects of a new type of laser time-of-flight mass spectrometer are described in this letter. It is based on a wedge-shaped reflecting mirror and is used as an ion analyzer. The analyzer provides time focusing by both energy and divergence angle of ions. Time focusing of good quality is acquired in the energy range of ±20% of the average ion energy, which is, at least, two times wider than the energy range of the known ion optical systems for similar applications. The mass resolution of the analyzer is ∼600, while overall dimensions are very small (10 × 10 × 5 cm).